2022
DOI: 10.1038/s41586-022-04665-6
|View full text |Cite
|
Sign up to set email alerts
|

A trail of dark-matter-free galaxies from a bullet-dwarf collision

Abstract: The ultra-diffuse galaxies DF2 and DF4 in the NGC 1052 group share several unusual properties: they both have large sizes1, rich populations of overluminous and large globular clusters2–6, and very low velocity dispersions that indicate little or no dark matter7–10. It has been suggested that these galaxies were formed in the aftermath of high-velocity collisions of gas-rich galaxies11–13, events that resemble the collision that created the bullet cluster14 but on much smaller scales. The gas separates from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 47 publications
(93 reference statements)
3
33
0
Order By: Relevance
“…Therefore, NLG predicts less effective dark matter for dwarf galaxies as compared with the standard picture. This prediction seems to be consistent with observational data regarding dwarf galaxies that lack dark matter (van Dokkum et al 2018;Guo et al 2019;Mancera Piña et al 2019;Hammer et al 2020;Shen et al 2021). In the next section, we apply NLG to three UDGs, namely, AGC 114905, 242019, and 219533 and compute their effective dark matter content.…”
Section: Effective Dark Matter Within a Galaxysupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, NLG predicts less effective dark matter for dwarf galaxies as compared with the standard picture. This prediction seems to be consistent with observational data regarding dwarf galaxies that lack dark matter (van Dokkum et al 2018;Guo et al 2019;Mancera Piña et al 2019;Hammer et al 2020;Shen et al 2021). In the next section, we apply NLG to three UDGs, namely, AGC 114905, 242019, and 219533 and compute their effective dark matter content.…”
Section: Effective Dark Matter Within a Galaxysupporting
confidence: 90%
“…This situation with NLG is in sharp contrast with the standard CDM paradigm, where the rotation curves can be fit very well; however, the resulting predicted total amount of dark matter for each UDG is too small by about an order of magnitude. This shortcoming, on the other hand, could be the result of the rare collision events recently proposed by van Dokkum et al (2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, hydrodynamical simulations [40,45,46] have shown that it is even possible to create a galaxy lacking DM in the standard cosmological scenario, and in [47][48][49] it has been suggested that NGC1052-DF2 may have formed as a consequence of high velocity collisions of gas-rich galaxies. In a most recent work [50], it was added that it might represent a sample of a possibly larger family, as a total of eleven low surface galaxies with the same properties have been found.…”
Section: Introductionmentioning
confidence: 99%